Perceraian dan Akibat Hukumnya terhadap Anak dan Harta Bersama Menurut Hukum Adat Osing di Desa Aliyan, Kecamatan Rogojampi, Kabupaten Banyuwangi - Ananta, Muhamad Jefri; Rato, Dominikus; Yasa, I Wayan (Lentera Hukum, 2017)
Divorce or dissolution of the marriage means the return of husband and wife into group family own. According to Osing adat law in Aliyan village, Rogojampi, Banyuwangi Regency, the divorce will give the rise to rights and obligations of children and joint property. The community of Osing adat law embraces the system of bilateral kinship which pulls the descendant line of the second parent with regard to the divorce by which children are given the freedom to choose by following the father or the mother. The community of Osing adat law never discriminates on the ground of biological children, legal children, adopted children and stepchildren, and legal position children. In the system of bilateral kinship, with regard to the divorce, the legal position of the property will return to the origin and joint property will be shared equally. Keywords: Divorce, Osing Adat Law, Legal Position, Children and Joint Property